2002
DOI: 10.22358/jafs/67791/2002
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and carcass characteristics of Awassi, Morkaraman and Tushin lambs grazed on pasture and supplemented with concentrat

Abstract: Growth performance (n=T58) and carcass characteristics of 5 Awassi (A), 5 Morkaraman (M) and 4 Tushin (T) lambs weaned at 2.5 months of age were evaluated. The lambs were fed a concentrate mixture and allowed to graze for 70 days. At the end of the 70-day grazing period, M lambs showed the highest daily weight gain and the amount of concentrate consumed per body weight gain. The effects of breed and sex of lamb on daily weight gain on pasture were significant (P<0.05) and highly significant (PO.01), respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…Payne (1999) also reported that dressing percentage increases with increasing the proportions of concentrate in the ration. The dressing percentage on slaughter weight base and empty body weight base in this experiment was relatively small in all treatments than the results reported by Monaem et al (1988) for Moghani rams; Galal and Kassahun (1981) for Ethiopian highland sheep and Horro sheep; and Macit et al (2002) for Awasi, Morkaraman, and Tushin lambs. Dressing percentage describes the carcass merit condition as a proportion of carcass weight to body weight which helps to assess the meat proportion of the animal subjectively (Getahun, 2006 andDevendra andBurns, 1983) The dressing percentage of this study on the basis of slaughter body weight were 35.29%, 37.56%, 39.46%, 43.00% and 45.03 for T 1 , T 2 , T 3 , T 4 , and T 5 , respectively.…”
Section: © Cncs Mekelle University 94 Issn:2220-184xcontrasting
confidence: 62%
“…Payne (1999) also reported that dressing percentage increases with increasing the proportions of concentrate in the ration. The dressing percentage on slaughter weight base and empty body weight base in this experiment was relatively small in all treatments than the results reported by Monaem et al (1988) for Moghani rams; Galal and Kassahun (1981) for Ethiopian highland sheep and Horro sheep; and Macit et al (2002) for Awasi, Morkaraman, and Tushin lambs. Dressing percentage describes the carcass merit condition as a proportion of carcass weight to body weight which helps to assess the meat proportion of the animal subjectively (Getahun, 2006 andDevendra andBurns, 1983) The dressing percentage of this study on the basis of slaughter body weight were 35.29%, 37.56%, 39.46%, 43.00% and 45.03 for T 1 , T 2 , T 3 , T 4 , and T 5 , respectively.…”
Section: © Cncs Mekelle University 94 Issn:2220-184xcontrasting
confidence: 62%
“…The sex of lamb had a highly significant (P<0.01) effect on daily average weight gain. Male lambs were heavier (P<0.01) than female lambs, and they also grew faster than females (Macit, 2001).…”
Section: Effect Of Sex On Growth Ratementioning
confidence: 93%